A Self‐Healing Volume Variation Three‐Dimensional Continuous Bulk Porous Bismuth for Ultrafast Sodium Storage. (26th March 2021) - Cheng, Xiaolong; Shao, Ruiwen; Li, Dongjun; Yang, Hai; Wu, Ying; Wang, Bin; Sun, Chunhao; Jiang, Yu; Zhang, Qiaobao; Yu, Yan
Abstract: Bismuth (Bi) has attracted considerable attention as promising anode material for sodium‐ion batteries (NIBs) owing to its suitable reaction potential and high volumetric capacity density (3750 mA h cm −3 ). However, the large volumetric expansion during cycling causes severe structural degradation and fast capacity decay. Herein, by rational design, a self‐healing nanostructure 3D continuous bulk porous bismuth (3DPBi) is prepared via facile liquid phase reduction reaction. The 3D interconnected Bi nanoligaments provide unblocked electronic circuits and short ion diffusion path. Meanwhile, the bicontinuous nanoporous network can realize self‐healing the huge volume variation as confirmed by in situ and ex situ transmission electron microscopy observations. When used as the anode for NIBs, the 3DPBi delivers unprecedented rate capability (high capacity retention of 95.6% at an ultrahigh current density of 60 A g −1 with respect to 1 A g −1 ) and long‐cycle life (high capacity of 378 mA h g −1 remained after 3000 cycles at 10 A g −1 ). In addition, the full cell of Na3 V2 (PO4 )3 |3DPBi delivers stable cycling performance and high gravimetric energy density (116 Wh kg −1 ), demonstrating its potential in practical application. Abstract : A 3D continuous bulk porous bismuth anode (3DPBi) is prepared via liquid phase reduction reaction. Owing to the bicontinuous nanoporous network, the 3DPBi anode can realize self‐healing the huge volume variation and exhibit unprecedented sodium‐storage performance in terms of rate performance (capacity retention of 95.6% at 60 A g −1 ) and cycle life.